SINTESIS DAN KARAKTERISASI MATERIAL MAGNETIK BARIUM HEXAFERRITE TERSUBSTITUSI MENGGUNAKAN TEORI SOLGEL UNTUK APLIKASI SERAPAN GELOMBANG MIKRO PADA FREKUENSI X-BAND - Sulistyo, Sulistyo; Marhaendrajaya, Indras; Priyono, Priyono (BERKALA FISIKA, 2012)
The Barium hexaferrite well known by permanen magnet which have prime properties for microwave application. The properties of Barium hexaferrite modified by substitution of MnCo and Ti have been investigated. Material was produced by sol-gel processing. Analysis of composition, crystal structure, refinement, microstructure and grain size, hysterisies and microwave characteristic respectively done by means of EDX, XRD, GSAS, SEM, magnetometers and wave guide at frequency1-17GHz. The formed crystal structure were hexagonal with the grain size is 500 nm, saturation magnetisation, field of coercivities , and remaneninduction respectively is 0.32 T, 3.8 kA/m and 0.04 T. The substitution of Fe3+ ion, resulted on decreasing the value of Ms, Hc , Rr and range of microwave absorbtion respectively. The maximum absorbtion of microwave occured on frequency 13.6 GHz.Keywords : barium hexaferrite, permanen magnet, sol-gel method, microwave